Penilaian Petani Terhadap Multifungsi Pertanian Padi Sawah Anorganik Dan Organik Di Desa Tonusu Kecamatan Pamona Puselemba - Marianne Reynelda Mamondol; Silvany Annatje Taariwuan (Agropet, 2015)
The purposes of this research are to find out the differences of the knowledge and assessment owned and given by inorganic and organic rice field farmers on the functions of rice field farming in terms of economic, social-cultural, and environmental aspects. Primary data is collected from rice field farmers in Tonusu Village through survey, using questionnaire and interview. 20 farmers determined as respondents through quota sampling, consist respectively of 10 farmers who applying inorganic and organic rice farming. Study is conducted by identifying the agriculture multifunctionality  on the aspects of economic, social-cultural, and environment.  Data is analyzed descriptively and tested with t test for 2 independent samples. Result demonstrates that there is difference of the knowledge between inorganic and organic farmers on the functions of rice field farming.  The average number of functions known by inorganic respondents is  71,56 %, less than that of organic respondents with the value of 91,67 %, particularly on the functions of farm women’s role, soil quality, biodiversity, environment pollution indicator, and food security. Besides, there is difference of the assessment made by both groups on the application of the rice field functions.  The average of functions given high assessment by inorganic respondents is 27,08 %, less than that of organic respondents with the value of 46,04 %, on the functions of farmer solidarity, soil quality, biodiversity, environment pollution indicator, farming attraction, and food security. Therefore, the agriculture multifunctionality in organic rice field farming is better than that of the inorganic system.